2021
DOI: 10.1101/2021.01.02.21249141
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Diagnostic performance and clinical implications of rapid SARS-CoV-2 antigen testing in Mexico using real-world nationwide COVID-19 registry data

Abstract: BACKGROUNDSARS-CoV-2 testing capacity is important to monitor epidemic dynamics. Given difficulties of large-scale RT-PCR implementation, rapid antigen tests (Rapid Ag-T) have been proposed as alternatives in settings such as Mexico.OBJECTIVESTo evaluate diagnostic performance of Rapid Ag-T for SARS-CoV-2 infection and its associated clinical implications compared to RT-PCR testing in Mexico.METHODSWe analyzed data from the COVID-19 registry of the Mexican General Directorate of Epidemiology up to December 31s… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 31 publications
(36 reference statements)
3
4
0
Order By: Relevance
“…All three studies also report similar ability to detect lower Ct values with higher sensitivity. Although our study involved mainly white British people, comparable results have been recorded in other countries and ethnic groups 2627…”
Section: Discussionsupporting
confidence: 81%
“…All three studies also report similar ability to detect lower Ct values with higher sensitivity. Although our study involved mainly white British people, comparable results have been recorded in other countries and ethnic groups 2627…”
Section: Discussionsupporting
confidence: 81%
“…Findings regarding between-variants difference for SARS-CoV-2 corroborated previous literature indicating that Omicron or Omicron period infections were associated with reduced likelihood of PCC compared to earlier variants (9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20). In the present study, however, the ability to disaggregate Omicron sub-variants found that infection during the Omicron BA.1 period was associated with greater likelihood of PCC compared to subsequent Omicron periods.…”
Section: Key Findings and Interpretationsupporting
confidence: 88%
“…24 Therefore, some limitations should be considered: first, early in the pandemic, testing was reserved for higher risk cases, which likely skewed risk assessment towards higher risk cases and may have improved later in the pandemic with the implementation of rapid antigen testing. 25 Second, attainment of the differences in CFR risk within healthcare subsystems is complex and cannot be uniquely assigned to differences in access or quality of care but also to admission criteria, severity spectrum of admitted cases and local influence of pandemic dynamics. Third, although cases with ambulatory care often indicate cases with milder presentations of Covid-19, initially asymptomatic or milder cases may not be fully accounted for in second and third level care clinics, which may explain the increased risk in those institutions.…”
Section: Discussionmentioning
confidence: 99%